The Experience of International Students and Institutional Recommendations: A Comparison Between the Students From the Developing and Developed Regions - Qadeer, Talat; Javed, Muhammad Kashif; Manzoor, Aqsa; Wu, Min; Zaman, Syed Imran (Frontiers in Psychology, 2021)
Prior studies on the experiences of international students in China have mostly focused on their academic, sociocultural, and accommodation experiences. Hence, student health and safety, discrimination, and the services by the International Student Office (ISO) have remained unexplored. Moreover, due to the motivational differences between the students from developing and developed regions, a study that samples students from both regions may depict an exact picture of international students’ experience. Therefore, the objective of this study is to examine the influence of the dimensions (including those dimensions that have been ignored) of international students’ experience on their satisfaction. In addition, we make recommendations regarding Chinese institutes to future students based on a comparison between the students from developing and developed regions. Using hierarchical regression analysis, this study reveals that educational and non-educational experiences vary among students from different regions. Therefore, on the basis of developing (e.g., Asia and Africa) and developed (e.g., America, Europe, and Australia) regions, important recommendations are discussed regarding how educational institutions and the Chinese government could best allocate resources and introduce policies to improve the experience of international students.